Giving up the ghost a memoir - Mantel, Hilary 1952-2022 (Henry Holt, 2003)
An award-winning author and reviewer describes her tomboy childhood, challenging Catholic school education, broken family life, marriage, struggle with chronic illness which rendered her unable to have children, and literary career.
"A John Macrae book.".
Keywords: Mantel, Hilary <1952->; Mantel, Hilary <1952-> -- Childhood and youth; Mantel, Hilary <1952-> -- Family; Mantel, Hilary -- 1952-2022; Geschichte 1900-2000; Chronic pain -- Patients -- Great Britain -- Biography; Novelists, English -- 20th century -- Biography; Großbritannien; Biografie